2023
DOI: 10.1186/s40359-023-01040-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-critical perfectionism mediates the relationship between self-esteem and satisfaction with life in Lebanese university students

Abstract: Background The psychological mechanisms that underlie the relationship between self-esteem and life satisfaction remain unclear and not well-understood. We sought through the present study to test the hypothesis that perfectionism plays a significant mediating role in the association between self-esteem and satisfaction with life among Lebanese university students. Methods A cross-sectional study was performed in a sample of 363 students (61.7% fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…Strong meta-analytic evidence drawn from longitudinal studies [ 12 , 69 ] and meta-synthesis of qualitative studies [ 70 ] concluded that the multidimensional perfectionism serves as a risk factor for depressive and anxiety symptoms. As for findings on self-critical perfectionism, they concur with those of previous studies [ 48 , 67 , 71 ], suggesting this component as a critical factor in the prediction of psychopathology.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Strong meta-analytic evidence drawn from longitudinal studies [ 12 , 69 ] and meta-synthesis of qualitative studies [ 70 ] concluded that the multidimensional perfectionism serves as a risk factor for depressive and anxiety symptoms. As for findings on self-critical perfectionism, they concur with those of previous studies [ 48 , 67 , 71 ], suggesting this component as a critical factor in the prediction of psychopathology.…”
Section: Discussionsupporting
confidence: 91%
“…Higher scores reflect higher perfectionism in the three aspects. We used the Arabic version of the scale, which was previously used [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the studies by Romdhane et al (2023) and Szczesniak et al (2022), a positive and significant association between life satisfaction and self-esteem was observed. This type of association was also found in the study by Bozoglan et al (2013).…”
Section: Discussionmentioning
confidence: 91%
“…Despite several studies showing that life satisfaction has a positive relationship with self-esteem (Bozoglan et al, 2013;Romdhane et al, 2023;Szczesniak et al, 2022), when attempting to understand interaction effects between self-esteem and participants' sociodemographic characteristics (gender versus self-esteem and age versus self-esteem) regarding their life satisfaction, these effects disappear. This may be justified by the fact that levels of life satisfaction and self-esteem vary from men to women and across different ages (Moksnes & Espnes, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, it is important to understand the effects of the COVID-19 pandemic on family dynamics (Martin-Storey et al, 2021) and academic programs on the mental health and well-being of college students (Lemyre et al, 2023). Therefore, university students should consider the effects of self-esteem and family satisfaction in order to improve their skills and expand their social roles (Fekih-Romdhane et al, 2023), understanding that self-esteem is strongly related to health (Karaca et al, 2019), academic performance (Zheng et al, 2020) and life satisfaction (Lau et al, 2020). In this sense, university authorities should incorporate awareness programs into the curriculum on the importance of proper self-esteem and adequate family satisfaction (Reić Ercegovac et al, 2021).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%